Contracting for Public Delivery: The Dynamics of Relational Governance and Power Asymmetry in Public Infrastructure Project - Hassan, Fazlur Rahman; Syaafrian, Dzulfian; Maharani, Dinda Ayu (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2025)
Government institutions often face a dilemma in providing goods and services: whether to ‘outsource’ or manage them ‘in-house’. Large-scale public services typically require complex contracts to ensure successful project completion. This study examines the dynamics of relational governance and power shifts that lead to contract failure using a mixed-method approach applied to a complex public service project in Jakarta, one of the largest metropolitan areas in the world. The findings indicate that a contractual win-win outcome can be achieved with strong governance rules, particularly relational governance. However, relational governance can weaken without robust contractual governance, particularly during conflicts or disputes. The study suggests that excessive power imbalance between the authority and the third party undermines bilateral relationships and long-term cooperation.